IL-1 stimulates ceramide accumulation without inducing apoptosis in intestinal epithelial cells - Fadia R. Homaidan; Marwan E. El-Sabban; Iman Chakroun; Mirvat El-Sibai; Ghassan S. Dbaibo (Hindawi Limited, 2002)
Background: In inflammatory bowel disease (IBD), cytokine levels (such as interleukin-1 (IL-1)) are elevated. We have shown previously that IL-1 activates phospholipid signaling pathways in intestinal epithelial cells (IEC), leading to increased ceramide levels.